Delayed lethal central nervous system toxicity induced by a low-dose intrathecal administration of bupivacaine: case report - Song, Weishang; Zhang, Hong; Li, Xiaohui; Yu, Chengxiang; Zhou, Yuhong; Li, Yuesu; Chen, Bing (Frontiers in Anesthesiology, 2023)
Spinal anesthesia by intrathecal administration of local anesthetic (LA) is a routine practice. Local anesthetic system toxicity, occurring in the central nervous system (CNS) and cardiovascular system, is a common and life-threatening adverse event of LA through a variety of routes, but is rarely encountered in spinal anesthesia when a very low dose of LA is injected into the subarachnoid space. Here, we report a case with manifestations of delayed lethal CNS toxicity after spinal anesthesia. A 55-year-old man underwent elective repair surgery for a chronic ulcer after receiving 10 mg intrathecal administration of bupivacaine. He developed nausea, agitation, paresthesia and myoclonus on the arms, legs, and trunk, as well as a gradually reduced level of consciousness one hour after intrathecal administration. He was sedated, intubated, and transferred to the intensive care unit. Both CT and MRI scans of the brain and assessments of blood showed no abnormalities. The electroencephalogram showed spike waves occurring at electrodes C3, C4, P3, P4, and T5. The patient was sedated continuously and treated with valproate. These symptoms were completely resolved in the following days without residual neurological complications. No cardiovascular complications were observed during the entire process. The delayed lethal symptoms in this case were most likely to be CNS toxicity induced by intrathecal bupivacaine administration. CNS toxicity after spinal anesthesia may be underestimated and unpredictable and should be vigilantly cared for in clinical settings.